Spear Fighting in the Military Art of the Kalmyks and Dzungars of the XVII – early XIX centuries - Bobrov Leonid A. (Монголоведение, 2023)
Introduction. The article examines the features of the formation and evolution of the Oirat light cavalry armed with spears of the Late Middle Ages and early Modern times. The purpose of the study is to identify the role of spear fighting in the military practice of the Dzungars and Kalmyks of the XVII – early XIX centuries on the basis of a comprehensive analysis of written, pictorial and material sources. Results. It has been established that in the Central Asian region for centuries shock spears and pikes remained mainly the weapons of armored cavalry, while light nomads without armor used them only sporadically. During the military transformations carried out by the Oirat and Mongol military leaders of the second half of the XVI–XVII centuries, mounted archers were equipped with shock spears and pikes, which led to the emergence of a new type of cavalry composed of lightly armed spearmen capable of conducting both remote and close combat. During the military campaigns of the Oirats, which covered most of steppe Eurasia, the idea of mass light cavalry with spears was adopted by many peoples of the Great Steppe, including Russian Cossacks and Turks of Eastern Europe (Nogais, Crimean and Polish-Lithuanian Tatars). In turn, the battle on the spears of the Polish-Lithuanian Tatars (Lipkov) formed the basis of the military practice of the Polish lancers, which became a model of such cavalry for the countries of Central and Western Europe of the XVIII – early XIX centuries. Based on the analysis of Mongolian, Oirat, Ottoman, European and Qing written sources, the original name of the Oirat long–barrel weapon of the XVII–XVIII centuries was revealed, which sounded like “jida” (“dzida”). The design features of the Oirat spears were established, the spear fighting technique and tactics of mounted Kalmyk and Dzungarian warriors armed with spears were reconstructed. Conclusions. The collected materials indicate that spears and pikes were the main type of melee weapons of the Oirat warriors of the XVII – early XIX centuries. Spear fighting was one of the key elements of the military art of the Dzungars and Kalmyks of this period. The Oirats had a significant impact on the development of the practice of equestrian spear fighting among the peoples of Eurasia of the XVII–XVIII centuries.